Fruit yield and quality of anise (Pimpinella anisum L.) in relation to agronomic and environmental factors - Ullah, Habib; Justus Liebig University Giessen (My University, 2012)
From 2008 to 2010 field experiments with the medicinal and spice plant Pimpinella anisum L. were carried out to clarify the effect of different agronomic factors on fruit yield and its components as well as on essential oil content and its composition. Three field experiments were carried out at two experimental stations in Giessen and Gross-Gerau. First experiment included three factors: sowing rates, sowing times and cultivars. Second experiment included different row spacing (15, 25 and 35.5 cm) and sowing rates (6, 12 and 24g/10 m2). Third field experiment was carried out to evaluate the efficacy of various fungicides against the fungal infection caused by Cercospora malkoffii. The field trials regarding sowing time and fungicide were designed in RCBD factorial plot arrangements whereas row spacing as under split plot arrangement with four replications. Anise fruits were hydro-distillated using a distillatory apparatus of Neo-Clevenger. The essential oil was analyzed by GC-FID and GC-MS. All data were statistically analyzed by using PIAF software.In the fungicide field experiments it was found that two of the tested fungicides Mancozeb + Metalaxyl-M and Azoxystrobin + Difenoconazol reduced Cercospora malkoffii severity to a great extent in both years. This was consistent over two seasons with different levels of disease in each. It was observed that applied fungicides had no significant impact regarding yield contributing parameters including primary branches, umbels, fruits and fruit weight per plant in 2009 whereas significantly effects were observed in 2010. Cultivar Pharmasaat was characterized by higher level of fruit yield parameters compared with cv. Enza Zaden in 2009. It was found that anise plants sprayed with Azoxystrobin + Difenoconazol induced higher fruit yield parameters compared with other fungicides. Further it was found that essential oil concentration of anise fruits was affected by fungicides as well by used cultivars in 2010. Plants treated with Azoxystrobin + Difenoconazol and Fosetyl accumulated significant more essential oil compared with other treatments. Contrary to that essential oil concentration of anise showed no remarkable variation regarding fungicides application in 2009. The compound trans-anethole reached maximal concentration in anise fruits of the plots which were applied with Fosetyl in both seasons. It can be concluded that Fosetyl improved host defense mechanism which could be a reason of higher level of trans-anethole in anis fruits.

In den Jahren 2008 bis 2010 wurden Feldversuche mit der Arznei- und Gewürzpflanze Pimpinella anisum L. durchgeführt, um den Einfluss unterschiedlicher agronomischer Faktoren auf den Fruchtertrag und die Ertragskomponenten sowie auf den Gehalt und die Zusammensetzung des ätherischen Öls dieser Pflanzen zu untersuchen. Es wurden drei Feldversuche in den Versuchsstationen Gießen (schluffiger Lehmboden) und Groß-Gerau (Sandboden) durchgeführt. Im ersten Versuch wurde die Wirkung der Prüffaktoren Saatmenge, Saatzeit und Sorte untersucht. Im zweiten Feldversuch wurden unterschiedliche Reihenentfernungen (15, 25 und 35 cm) mit drei Aussaatmengen (6, 12 und 24g/10 m2) kombiniert. Der dritte Feldversuch wurde durchgeführt, um die Wirksamkeit unterschiedlicher Fungizide auf die Infektion mit Cercospora malkoffii zu klären.Die durchgeführten Fungizidversuche brachten zum Ausdruck, dass die Wirkstoff-Mischungen Mancozeb + Metalaxyl-M sowie Azoxystrobin + Difenoconazol in beiden Versuchsjahren eine wirksame Verminderung der Infektion mit Cercospora malkoffii bewirkten. Im Jahr 2009 bewirkte die Applikation der Fungizide keine Veränderung der Ertragsparameter der Anispflanzen. Demgegenüber wurde im Jahr 2010 eine signifikante und positive Beeinflussung der Ertragsparameter durch die Wirkstoffe Azoxystrobin + Difenoconazol beobachtet. Darüber hinaus wurden im Jahr 2010 durch die Fungizide sowie durch die Sorten auch die Gehalte an ätherischem Öl beeinflusst. Die Wirkstoffe Azoxystrobin + Difenoconazol sowie Fosetyl bewirkten eine signifikante Zunahme der Ölakkumulation in den Anisfrüchten. Der Wirkstoff Fosetyl induzierte außerdem eine höhere Konzentration an trans-Anethol im ätherischen Öl, was mit der Stimulierung der Abwehrreaktion der Pflanze durch Abbau von Phosphorsäure begründet wird.
Keywords: ddc:630